The Role of Perceived Organizational Support and Interpersonal Justice in Shaping Affective Commitment Among Gen-Z Employees: The Mediating Effect of Intrinsic Motivation - Yongki Yuda Prawira; Diva Zahra Nirvana; Dedi Muhammad Siddiq; Tho Alang (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2026)
This study aims to investigate the influence of organizational support and interpersonal justice on affective commitment among Generation Z employees in the manufacturing sector, with intrinsic motivation examined as a mediating variable. Adopting a cross-sectional quantitative approach, the study surveyed 174 Gen-Z workers employed in manufacturing firms located in Cirebon, Indonesia. Data were analyzed using Structural Equation Modeling with the Partial Least Squares (PLS-SEM) technique via SmartPLS 3.0 software. The analysis comprised evaluations of the measurement model, structural model, mediation testing, and hypothesis verification. The results demonstrate that both organizational support and interpersonal justice exert significant positive effects on affective commitment, both directly and indirectly through intrinsic motivation. These findings highlight the pivotal role of supportive and fair workplace environments in cultivating intrinsic motivation and strengthening affective commitment among Gen-Z employees. The study offers practical insights for human resource strategies aimed at enhancing employee retention and engagement in labor-intensive industries.